Effect of preetching on microleakage with all-in-one adhesives using calcium-based desensitizers: An in vitro study - N Tulasi Priya; Harikumar Vemisetty; Keerthi Sudireddy; Jayaprada Reddy Surakanti; Amulya Vanapatla; Anil Kumar Maradi (Wolters Kluwer Medknow Publications, 2018)
Objectives: The aim of this study was to evaluate the effect of calcium-based desensitizers on the microleakage with and without preetching enamel in Class V cavities restored with all-in-one adhesives. Materials and Methods: Class V cavities were prepared on the buccal surfaces of 100 extracted human premolars. A total of 100 box-shaped cavities were divided into five groups (n = 20). Group 1 - no desensitizer was applied and Groups 2 and 4 - desensitizer (CCP-ACP and Novamin) was applied, respectively, followed by the application of G-Bond and restored with composite restoration. Groups 3 and 5 are same as Group 2 and 4, but preetching of enamel was done for 3 s after desensitizers application. The teeth were thermocycled and the specimens were examined for microleakage using methylene blue as a marker. The teeth were sectioned buccolingually and evaluated for microleakage under stereomicroscope and the scores obtained were analyzed with Kruskal-Wallis and Mann-Whitney tests. Results: Statistically significant difference existed between Groups 2 and 3 (P < 0.05). There was also statistically significant difference between Groups 4 and 5 (P < 0.05). Groups 3 and 5 showed significantly less microleakage (P < 0.05). No statistically significant difference in microleakage values was observed between the two desensitizers CCP-ACP and Novamin. Conclusion: The application of calcium-containing desensitizers with selective etch enamel technique in all-in-one adhesives could be considered an advisable procedure to minimize microleakage.